Role of Oxidative Stress in Outcome of Pregnancy Induced Hypertension Cases - Choudhary, Dr. Anjana; Jindal, Dr. Monika; Ratnani, Dr. Rekha (International Journal of Innovative Research in Medical Science, 2018)
Introduction Pregnancy induced hypertension (PIH) is one of the most frequent and most difficult illnesses in pregnancy, which jeopardizes both mother and fetus. Frequency is about 10% with significant variations in certain parts of the world depending on diagnostic criteria.[1] High risk pregnancy is defined as one which is complicated by factor or factors that adversely affects the pregnancy outcome either maternal or perinatal or both. The oxygen paradox underpins the biology of the whole free radical system. The role of free radicals can be traced back to the origin of life of earth. In a healthy body, ROS (reactive oxygen species) and antioxidants remain in balance. When the balance is disrupted towards an overabundance of ROS, oxidative stress (ROS) occurs. It plays very important role during pregnancy and normal parturition and in recurrent pregnancy loss, initiation of preterm labor, anaemia, preeclampsia, eclampsia, intrauterine growth retardation.